Oxidation of benzyl alcohol to benzaldehyde over MnOx/sepiolite catalysts - Nhu, Nguyen Thi; Anh, Quach Toan; Thao, Nguyen Tien (Vietnam Journal of Chemistry, 2017)
MnOx/sepiolite catalysts were synthesized by precipitation method accompanied by the calcination at 4100C. The prepated solids have been characterized by XRD, SEM, TPR-H2. MnOx particles were deposited on the surface of the sepiolite fibers and act as active sites for  the oxidation of benzyl alcohol using tert-butyl hydroperoxide (TBHP) as an oxidizing agent. The catalysts showed a good conversion of benzyl alcohol to benzaldehyde at 60 oC. The influence of the reaction time and reaction temperature was considered. Keywords. MnOx/sepiolite, oxidation, benzyl alcohol conversion, TBHP, benzaldehyde.